Halal Tourism: A Future Research Roadmap Based on Bibliometric Analysis - Supriyadi, Supriyadi; Rahman, Azibur (El-Qist: Journal of Islamic Economics and Business (JIEB), 2024)
This research aims to present a systematic literature review of halal tourism using bibliometric analysis to map its conceptual development, research trends, and future research opportunities within the global academic landscape. Drawing on 262 publications from the Scopus database between 2010 and August 2024, the study reveals significant growth in halal tourism scholarship, particularly in the fields of business, management, and social sciences, with Indonesia and Malaysia emerging as the dominant contributors. Through VOSviewer visualization, the analysis identifies leading authors, influential institutions, and recurring thematic clusters. The findings also uncover critical research gaps, notably the underrepresentation of themes such as religiosity, sustainability, policy making, and customer satisfaction in the halal tourism discourse. These gaps signal the need for a multidimensional research approach that includes qualitative perspectives, socio-cultural frameworks, and policy analysis. This study contributes to global knowledge by offering a comprehensive research roadmap that integrates economic, cultural, and spiritual dimensions of halal tourism. It recommends that future research expand into halal ecotourism, tourism management, and traveller behaviour to ensure inclusive and sustainable development of the industry. The proposed agenda serves as a reference point for scholars, policymakers, and tourism practitioners worldwide to align academic inquiry with emerging needs and global market shifts in Muslim-friendly tourism services.